GAYA KEPEMIMPINANDALAM MENINGKATKAN KINERJA STAF BALAI REHABILITASI SOSIAL ANAK YANG MEMERLUKAN PERLINDUNGAN KHUSUS (BRSAMPK)” RUMBAI” PEKANBARU - Nababan, Kertina; Jas, Jasfar; Sumardi, Sumardi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract:Based on interviews with some of the Social Rehabilitation Center Staff Children in Need of Special Protection (BRSAMPK) Jalan Rumbai Coastal School, Rumbai Beach, Pekanbaru, did not pay much attention to the dynamics and performance of staff in running the program, often authoritarian, unwilling to know, such as not accepting the opinions of subordinates, not responding the opinions of his subordinates. This type of research used in this research is descriptive using a quantitative approach. According to Sugiyono (Sugiyono: 2014: 49) This descriptive research aims to provide a systematic description of the situation that occurs in the research project, Leadership Style in Improving the Performance of Staff of the Social Rehabilitation Center for Children Needing Special Protection (BRSAMPK)